An improved perturb and observe checking algorithm MPPT for photovoltaic system under partial shading condition - Alik, R. (Institute of Electrical and Electronics Engineers Inc., 2016)
To have an efficient Photovoltaic (PV) system, Maximum Power Point Tracking (MPPT) technique is essential. Perturb and Observe (P&O) MPPT is not a new algorithm in the field of solar energy; nevertheless, it is said to be the simplest and low cost method for MPPT technique. However, its major drawbacks - steady state oscillation problem and failure to track maximum power point (MPP) under partial shading condition cause the PV system to become less efficient. Thus, this paper proposes a modified P&O MPPT that can be used under partial shading condition efficiently, by adding a simple checking algorithm to the P&O algorithm, in which the global maximum power point (MPP) is tracked first before the P&O algorithm takes place to produce optimum duty cycle for the boost converter. A Simulink model and simulation results from MATLAB/Simulink are also presented.